Born to be young? Prenatal thyroid hormones increase early-life telomere length in wild collared flycatchers. (25th November 2020) - Stier, Antoine; Hsu, Bin-Yan; Marciau, Coline; Doligez, Blandine; Gustafsson, Lars; Bize, Pierre; Ruuskanen, Suvi
Abstract : The underlying mechanisms of the lifelong consequences of prenatal environmental condition on health and ageing remain little understood. Thyroid hormones (THs) are important regulators of embryogenesis, transferred from the mother to the embryo. Since prenatal THs can accelerate early-life development, we hypothesized that this might occur at the expense of resource allocation in somatic maintenance processes, leading to premature ageing. Therefore, we investigated the consequences of prenatal TH supplementation on potential hallmarks of ageing in a free-living avian model in which we previously demonstrated that experimentally elevated prenatal TH exposure accelerates early-life growth. Using cross-sectional sampling, we first report that mitochondrial DNA (mtDNA) copy number and telomere length significantly decrease from early-life to late adulthood, thus suggesting that these two molecular markers could be hallmarks of ageing in our wild bird model. Elevated prenatal THs had no effect on mtDNA copy number but counterintuitively increased telomere length both soon after birth and at the end of the growth period (equivalent to offsetting ca 4 years of post-growth telomere shortening). These findings suggest that prenatal THs might have a role in setting the 'biological' age at birth, but raise questions about the nature of the evolutionary costs of prenatal exposure to high TH levels.